Temporal variation in the chemical composition of Nassella trichotoma under a defoliation gradient - García, Andrés (2025)
Fluctuations in the chemical composition of invasive species can identify windows where grazing implementation can be maximised for improved weed management. Our goal was to determine the chemical composition of Nassella trichotoma (Nees) Hack. ex Arechav., an aggressive invasive grass species, after being subjected to either high or low defoliation across a defoliation intensity gradient and leaves were harvested over the growing season. All samples were analysed for protein content (PC) and neutral detergent fibre (NDF), acid detergent fibre (ADF) and acid detergent lignin (ADL) content. PC was generally higher, and NDF and ADF were higher in defoliated compared with undefoliated plants. An induced anti-herbivore defence may explain the increase in fibre content in response to defoliation, which would accentuate the low nutritional quality of N. trichotoma and, thus, its avoidance by cattle. Therefore, efforts should focus on preventing N. trichotoma leaf tissues from losing nutritional quality by integrating control measures, such as grazing regrowing shoots after disturbances that cause severe defolia-tion (e.g. burning) from early autumn to early spring. This approach could effectively reduce N. trichotoma competitiveness, preventing its persistence and spread.